Metastatic pediatric alveolar soft part sarcoma: a rare case report highlighting multidisciplinary treatment, molecular diagnostics, and novel therapeutic approaches - Çalışkan Kamış, Şule; Yağcı, Begül (Frontiers in Pediatrics, 2025)
BackgroundAlveolar soft part sarcoma (ASPS) is an extremely rare soft tissue sarcoma, accounting for less than 1% of all soft tissue sarcomas. Approximately 5%–10% of ASPS cases occur in children and adolescents. Despite its indolent local course, its high metastatic potential necessitates comprehensive, multidisciplinary management.Case presentationWe present a pediatric patient diagnosed with metastatic ASPS originating from the left thigh. Initial management included wide local excision and adjuvant radiotherapy. Immunohistochemistry demonstrated strong nuclear TFE3 positivity, supporting the diagnosis. Although FISH analysis for ASPSCR1–TFE3 fusion was planned, technical limitations prevented archival imaging. Despite initial local control, the patient developed pulmonary, hepatic, brain, and intraabdominal metastases during follow-up. Serial imaging, including 18F-FDG PET/CT and brain MRI, revealed progressive disease with increasing metastatic burden in the lungs, mediastinum, brain, and distal colon. The patient underwent multiple systemic treatments over approximately 30 months, including tyrosine kinase inhibitors, an mTOR inhibitor (sirolimus), and immune checkpoint inhibition (pembrolizumab), alongside multiple courses of radiotherapy. The entire treatment timeline illustrates the complex, multidisciplinary management required for this ultra-rare malignancy.ConclusionThis case highlights the critical role of histopathological and molecular confirmation, multidisciplinary care, and emerging targeted and immunotherapy approaches in pediatric ASPS. Collaborative multicenter trials are urgently needed to establish evidence-based treatment strategies for this challenging disease.